Analisis Potensi Pasar Tradisional dalam Meningkatkan Perekonomian Daerah - Sumiati; Sulkarnain; Sitti Jamilah Amin; Damirah (Institut Agama Islam Negeri Parepare, 2022)
The potential of the market must be developed properly to improve the community's economy in accordance with Islamic law. The purpose of this study is to determine the potential of the market and the perspective of Islamic economic views on traditional markets in the Sidenreng Rappang area, especially in the Rappang area. By understanding the market's potential, it is hoped that the community can maximize management to have an impact on improving their economy. The research was conducted at the Rappang Central Market using a qualitative method with a sociological approach and data collection techniques through surveys, literature studies, observations, and interviews. The results showed that the Rappang Central Market has the potential to improve the economy of traders in the market by looking at the absorption of local commodities, as well as a short supply chain of basic needs from suppliers to consumers, having market segmentation in the area and increasing business opportunities for women. So, by maximizing the potential that exists in the Rappang Central Market is able to play a role in increasing the economic independence of the people around the Rappang Central Market. The results of research on the perspective of sharia economic views show that buying and selling transactions both in terms of merchandise sold, weighing tools, usury and Gharar, prices, and business ethics of traders at the Rappang Central Market do not violate Islamic law. The results of this study can be used as input for stakeholders to pay attention to the regional economy which is supported by traditional markets.